Juridical Review of the Mechanism of Asset Return in Corruption as an Effort to Recovery of State Losses - Bambang Budi Priyanto; Faisal Santiago; Evita Isretno Israhadi (CV. Publikasi Indonesia, 2023)
The criminal act of corruption is one part of a special crime, in addition to having certain specifications that are different from general crimes, namely with deviations from formal criminal law or procedural law. Corruption cases in this country still occur as if dominating crimes in Indonesia. This research is a descriptive analytical research, namely a study that presents phenomena or symptoms and actual circumstances about the mechanism of financial returns and / or state assets resulting from criminal acts of corruption. Law Number 20 of 2001 concerning the criminal act of corruption which in Article 18 is explained related to additional crimes as one of the efforts to recover State finances, Law Number 7 of 2006 concerning the Ratification of the United Nations Convention Against Corruption 2003 (United Nations Convention Against Corruption 2003) which explains that the seizure of assets of perpetrators of corruption crimes can be carried out through criminal and civil channels, Another regulation is Law Number 1 of 2006 concerning mutual assistance in criminal matters which is the legal basis for the Indonesian government in requesting and/or providing mutual assistance as well as a guideline for making agreements in criminal matters with Foreign Countries. In this case, the return of assets in corruption crimes can be carried out through several channels/instruments, including through criminal, civil and administrative channels.